A low-temperature processed high-transparency random copolymer polypropylene based on unipol process and a preparation method thereof
Patent Information
- Application Number
- CN202611240754.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-20
AI Technical Summary
然而,现有技术在追求高透明性的过程中,往往忽视了对力学性能的兼顾
1、在无规共聚聚丙烯体系中引入氢化C9石油树脂后,材料的透明性得到了进一步提升,其根本原因在于该树脂对聚丙烯结晶行为的调控作用。氢化C9石油树脂是一种完全非晶态的低分子量聚合物,其折射率约与聚丙烯基体的折射率非常接近。在熔融共混过程中,石油树脂分子均匀分散在聚丙烯基体中,冷却结晶时被排斥到球晶间的非晶区域,这一过程相当于对可结晶链段进行了稀释,单位体积内能够参与结晶的聚丙烯链段数量减少了,球晶生长受到空间上的限制,最终形成的球晶尺寸更小、数量更多,分布也更加均匀。球晶尺寸的减小是透明性改善的关键,当球晶尺寸缩小至可见光波长以下(≤400nm)时,散射体尺寸远小于入射光波长,散射效率急剧下降,光线在穿过材料时发生散射的概率大幅降低。加上石油树脂本身与聚丙烯非晶区的折射率差值很小,不会形成新的散射中心,二者的协同效果使得材料的雾度在原有基础上进一步降低,透明性改善效果明显且稳定。
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polypropylene technology, specifically to a low-temperature processed high-transparency random copolymer polypropylene based on the Unipol process and its preparation method. Background Technology
[0002] Polypropylene (PP) is one of the five major general-purpose plastics, widely used in packaging, home appliances, automobiles, and medical fields due to its excellent chemical stability, good molding and processing properties, and low production cost. However, as a semi-crystalline polymer, polypropylene exhibits a significant difference in refractive index between its crystalline and amorphous regions. Light refracts and scatters at the interface between these two phases when passing through the material, resulting in low transparency and severely limiting its application as a substitute for materials such as glass and polycarbonate in high-end transparent products. Random copolymerization modification is the mainstream technical route for improving the transparency of polypropylene. By introducing a small amount of ethylene comonomer during propylene polymerization, the regularity of the polypropylene molecular chain can be disrupted, reducing crystallinity and spherulite size, thereby improving transparency. The Unipol gas-phase process, due to its simplified process, large single-line capacity, and low investment cost, has become one of the mainstream processes for petrochemical companies to produce random copolymer polypropylene. In recent years, with the development and application of novel sorbitol-based nucleating and clarifying agents (such as sorbitol-based disubstituted derivatives), it has become possible to prepare highly transparent random copolymer polypropylene based on the Unipol process at a low temperature of 200℃. The haze of 1mm thin films can be reduced to 5-7%, achieving significant progress in energy saving and consumption reduction. However, in pursuing high transparency, existing technologies often neglect the consideration of mechanical properties. Random copolymerization modification itself reduces the crystallinity of polypropylene, and crystalline regions are precisely the main contributors to the mechanical strength of polypropylene. The reduction in crystallinity directly leads to varying degrees of decrease in the tensile strength, flexural modulus, and hardness of the material. Although nucleating and clarifying agents can improve mechanical properties to some extent by refining spherulites, their effect is limited and cannot completely compensate for the mechanical losses caused by random copolymerization. For high-end applications such as medical device shells that require both high transparency and high mechanical strength, relying solely on polymerization process optimization and nucleating and clarifying agents is no longer sufficient to meet increasingly stringent performance requirements. Summary of the Invention
[0003] The purpose of this invention is to provide a low-temperature processed high-transparency random copolymer polypropylene based on the Unipol process and its preparation method, so as to solve the technical problems mentioned in the background.
[0004] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a gas-phase fluidized bed reactor, propylene and ethylene monomers are copolymerized under the action of a catalyst to obtain random copolymer polypropylene powder. S2. Add hydrogenated petroleum resin to the random copolymer polypropylene powder and mix evenly to obtain the first mixture. S3. Add nano-calcium carbonate to the first mixture and mix evenly to obtain the second mixture; S4. Add ethylene-acrylic acid copolymer and ethylene-vinyl acetate copolymer to the second mixture in sequence, mix evenly, and obtain the third mixture. S5. Add nucleating and clarifying agents and processing aids to the third mixture, mix evenly, and then perform melt extrusion granulation. The maximum temperature of the extrusion granulation process shall not exceed 200°C to obtain highly transparent random copolymer polypropylene particles.
[0005] Preferably, the molar ratio of propylene to ethylene in step S1 is (38-45):1.
[0006] Preferably, the catalyst in step S1 is a Ziegler-Natta catalyst; The copolymerization conditions are as follows: reactor temperature controlled at 60-63℃, and total reaction pressure at 3.20-3.45MPa.
[0007] Preferably, the hydrogenated petroleum resin in step S2 is a hydrogenated C9 petroleum resin with a number-average molecular weight of 800-1500.
[0008] Preferably, the mass ratio of the random copolymer polypropylene powder to the hydrogenated petroleum resin is 100:(3-6).
[0009] Preferably, the mass ratio of the random copolymer polypropylene powder to nano-calcium carbonate in step S3 is 100:(2-5). Preferably, the nano-calcium carbonate is surface-treated activated nano-calcium carbonate with a particle size of 40–80 nm and a specific surface area ≥20 m². 2 / g; The active nano-calcium carbonate is stearic acid-modified nano-calcium carbonate.
[0010] Preferably, in step S4, the amount of ethylene-acrylic acid copolymer added is 0.5-1.5 wt% of the random copolymer polypropylene powder, and the amount of ethylene-vinyl acetate copolymer added is 1-3 wt% of the random copolymer polypropylene powder. The ethylene-acrylic acid copolymer contains 6-10 wt% acrylic acid; the ethylene-vinyl acetate copolymer contains 18-28 wt% vinyl acetate.
[0011] Preferably, the nucleating and clarifying agent in step S5 is a sorbitol disubstituted derivative; based on 100 parts by mass of the random copolymer polypropylene powder, the amount of the nucleating and clarifying agent added is 2200-3000 ppm.
[0012] Preferably, the nucleating and clearing agent is di(4-propoxybenzyl)sorbitol; The processing aids include primary antioxidants, secondary antioxidants, acid removers, and release agents; The primary antioxidant is a hindered phenolic antioxidant, the secondary antioxidant is a phosphite antioxidant, the acid remover is calcium stearate, and the release agent is monoglyceride.
[0013] A low-temperature processed, highly transparent random copolymer polypropylene based on the Unipol process was prepared by the method described above.
[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. The introduction of hydrogenated C9 petroleum resin into the random copolymer polypropylene system further improves the transparency of the material. This is fundamentally due to the resin's regulatory effect on the crystallization behavior of polypropylene. Hydrogenated C9 petroleum resin is a completely amorphous low-molecular-weight polymer with a refractive index very close to that of the polypropylene matrix. During melt blending, petroleum resin molecules are uniformly dispersed in the polypropylene matrix. During cooling and crystallization, they are repelled into the amorphous regions between spherulites. This process is equivalent to diluting the crystallizable segments, reducing the number of polypropylene segments capable of crystallization per unit volume. Spherulite growth is spatially restricted, resulting in smaller, more numerous, and more uniformly distributed spherulites. The reduction in spherulite size is key to improved transparency. When the spherulite size shrinks to below the visible light wavelength (≤400nm), the scatterer size is much smaller than the incident light wavelength, leading to a sharp decrease in scattering efficiency and a significant reduction in the probability of light scattering as it passes through the material. In addition, the refractive index difference between petroleum resin and the amorphous region of polypropylene is very small, so no new scattering centers will be formed. The synergistic effect of the two further reduces the haze of the material on the original basis, and the improvement in transparency is obvious and stable.
[0015] 2. The enhancing effect of nano-calcium carbonate on the mechanical properties of random copolymer polypropylene essentially stems from the interfacial effect and stress transfer mechanism between nanoscale rigid particles and the polymer matrix. Nano-calcium carbonate with a particle size of 40–80 nm possesses an extremely high specific surface area. When these particles are well-dispersed within the polypropylene matrix, a confined interfacial layer forms around each particle. Within this layer, the movement of polypropylene molecular chains is restricted, effectively increasing the local crosslinking density. When the material is subjected to tensile or bending loads, stress is transferred from the soft polymer matrix to the rigid inorganic particles through these interfacial layers. Nano-calcium carbonate bears part of the load, reducing stress concentration in the matrix. Simultaneously, when cracks propagate within the material, they are deflected and pinned by well-dispersed nanoparticles, making the crack propagation path more tortuous and consuming more fracture energy, thus improving the material's fracture resistance. It should be noted that the effect of rigid inorganic fillers on impact toughness is complex. While the crack deflection and pinning effects of nano-calcium carbonate contribute to improved toughness, the rigid filler itself also introduces stress concentration points. The actual effect is that the notched impact strength remains basically unchanged, while the subsequently introduced EVA / EAA interface modification layer provides additional rubber elastic toughening contribution, which further improves the impact toughness of the final product on the basis of CaCO3 stiffening, achieving a good balance between rigidity and toughness.
[0016] 3. Due to the low melt viscosity of the introduced hydrogenated petroleum resin, the locally formed enriched regions alter the local flow field environment around the calcium carbonate particles, hindering particle dispersion and stability. During melt processing, active nano-calcium carbonate easily aggregates and clumps together, forming aggregates hundreds of nanometers or even micrometers in size. The refractive index of these aggregates differs significantly from that of the polypropylene matrix, directly becoming light scattering centers, increasing product haze, and severely affecting the optical quality of the product. To solve this technical problem, this invention employs a step-by-step feeding method in step S4. First, the ethylene-acrylic acid copolymer is pre-mixed and dispersed with the second mixture containing nano-calcium carbonate, ensuring that the EAA powder is spatially close to the nano-calcium carbonate particles. Then, ethylene-vinyl acetate copolymer powder is added for a secondary pre-mixing and dispersion. In the subsequent melt extrusion step S5, under high-temperature melting and strong shearing, the polymer chains gain sufficient mobility. Due to the strong polar affinity between the carboxyl groups in EAA and the calcium carbonate surface, coupled with the spatial proximity advantage given to EAA and calcium carbonate particles in the S4 dry mixing stage, the EAA melt can preferentially adsorb and coat the surface of the nano-calcium carbonate particles to form a dense inner layer. Subsequently, the EVA melt continues to coat the outer layer of EAA to form a flexible outer layer. Finally, a synergistic interface modification layer characterized by an EAA-enriched inner region and an EVA-enriched outer region is constructed on the surface of each nano-calcium carbonate particle. This coating layer, on the one hand, erects a spatial barrier between particles and prevents aggregation; on the other hand, the refractive indices of EVA and EAA are very close to those of the polypropylene matrix. The coating layer effectively isolates the high-refractive-index surface of the calcium carbonate particles from the matrix, smoothing out the abrupt change in refractive index at the interface, and the light scattering effect is greatly reduced. The final result is that the haze of the product no longer increases significantly after the addition of nano-calcium carbonate, and the enhancement effect of mechanical properties is fully preserved, truly achieving a balance between high transparency and high strength. Attached Figure Description
[0017] Figure 1 This is a SEM image of the highly transparent random copolymer polypropylene prepared in Example 1 of the present invention. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1 A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a Unipol gas-phase fluidized bed reactor, using a Ziegler-Natta catalyst (TiCl4 / MgCl2 supported catalyst) as the main catalyst, triethylaluminum as the co-catalyst (Al / Ti molar ratio = 60), and dicyclopentyldimethoxysilane as the external electron donor (Al / Si molar ratio = 8), polymer-grade propylene and polymer-grade ethylene are continuously fed into the reactor at a molar ratio of 40:1 for copolymerization. The reactor temperature is controlled at 62℃, the total reaction pressure at 3.3MPa, and the hydrogen and nitrogen atmospheres are controlled at 0.8% and 23.8% respectively. The polymerization time is 1.0 h. The polymer powder is discharged intermittently from the reactor to the product degassing chamber through a PDS discharge system. Nitrogen is injected to remove hydrocarbons, and high-temperature steam is injected to deactivate the catalyst, yielding random copolymer polypropylene powder.
[0020] S2. Based on 100 parts by mass of the above random copolymer polypropylene powder, add 5 parts by mass of hydrogenated C9 petroleum resin fine powder (softening point 110℃, number average molecular weight 1000, pre-ground to 150 mesh) to a high-speed mixer and mix for 15 minutes at a speed of 900 r / min and a temperature of 60℃. During the mixing process, turn on the cooling water jacket to control the temperature and obtain the first mixture.
[0021] S3. Take nano-calcium carbonate powder (particle size 60nm, specific surface area 20m²). 2 The nano-calcium carbonate (6g) was placed in a high-speed modifier and heated to 110°C. Stearic acid (1.2wt% of the nano-calcium carbonate mass) was pre-melted at 85°C and then uniformly sprayed into the modifier using an atomizing spray method. The mixture was mixed and modified for 25 minutes at a stirring speed of 1200 r / min. After cooling to room temperature, the mixture was mechanically pulverized and depolymerized to obtain active nano-calcium carbonate powder. Four parts by mass of the above active nano-calcium carbonate were added to the first mixture and mixed for 10 minutes in a high-speed mixer at a speed of 700 r / min and a temperature of 55°C to obtain the second mixture.
[0022] S4. First, add 1.2 parts by mass of ethylene-acrylic acid copolymer powder (acrylic acid content 8wt%) to the second mixture, and mix in a high-speed mixer at a speed of 800 r / min and a temperature of 60℃ for 4 min to ensure full contact with the nano-calcium carbonate powder; then add 2.5 parts by mass of ethylene-vinyl acetate copolymer powder (vinyl acetate content 20wt%), and continue mixing for 6 min, for a total mixing time of 10 min, to obtain the third mixture.
[0023] S5. Add the following additives to the third compound (based on 100 parts by weight of random copolymer polypropylene powder): 2800 ppm di(4-propoxybenzyl)sorbitol, 1000 ppm antioxidant 1010 (hindered phenol), 1000 ppm antioxidant 168 (phosphite), 600 ppm calcium stearate, and 400 ppm monoglyceride. Mix in a high-speed mixer at 900 r / min and 55°C for 12 min, then feed into a twin-screw extruder for melt extrusion granulation. The extruder temperatures (from feed section to die head) are controlled as follows: 170°C, 185°C, 185°C, 188°C, 188°C; screw speed: 230 r / min; vacuum level at the exhaust port: -0.08 MPa. The extruded melt was granulated underwater, cooled in a cooling water bath (water temperature 25℃), and air-dried at 45℃ for 12 minutes to obtain highly transparent random copolymer polypropylene granules.
[0024] Example 2 A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a Unipol gas-phase fluidized bed reactor, using a Ziegler-Natta catalyst (TiCl4 / MgCl2 supported catalyst) as the main catalyst, triethylaluminum as the co-catalyst (Al / Ti molar ratio = 60), and dicyclopentyldimethoxysilane as the external electron donor (Al / Si molar ratio = 8), polymer-grade propylene and polymer-grade ethylene are continuously fed into the reactor at a molar ratio of 40:1 for copolymerization. The reactor temperature is controlled at 62℃, the total reaction pressure at 3.3MPa, and the hydrogen and nitrogen atmospheres are controlled at 0.8% and 23.8% respectively. The polymerization time is 1.0 h. The polymer powder is discharged intermittently from the reactor to the product degassing chamber through a PDS discharge system. Nitrogen is injected to remove hydrocarbons, and high-temperature steam is injected to deactivate the catalyst, yielding random copolymer polypropylene powder.
[0025] S2. Based on 100 parts by mass of the above random copolymer polypropylene powder, add 4 parts by mass of hydrogenated C9 petroleum resin fine powder (softening point 110℃, number average molecular weight 1000, pre-ground to 150 mesh) to a high-speed mixer and mix for 15 minutes at a speed of 900 r / min and a temperature of 60℃. During the mixing process, turn on the cooling water jacket to control the temperature and obtain the first mixture.
[0026] S3. Take nano-calcium carbonate powder (particle size 60nm, specific surface area 20m²). 2The nano-calcium carbonate (6g) was placed in a high-speed modifier and heated to 110°C. Stearic acid (1.2wt% of the nano-calcium carbonate mass) was pre-melted at 85°C and then uniformly sprayed into the modifier using an atomizing spray method. The mixture was mixed and modified for 25 minutes at a stirring speed of 1200 r / min. After cooling to room temperature, the mixture was mechanically pulverized and depolymerized to obtain active nano-calcium carbonate powder. Three parts by mass of the above active nano-calcium carbonate were added to the first mixture and mixed for 10 minutes in a high-speed mixer at a speed of 700 r / min and a temperature of 55°C to obtain the second mixture.
[0027] S4. First, add 0.8 parts by mass of ethylene-acrylic acid copolymer powder (acrylic acid content 8wt%) to the second mixture, and mix in a high-speed mixer at a speed of 800 r / min and a temperature of 60℃ for 4 min to ensure full contact with the nano-calcium carbonate powder; then add 1.5 parts by mass of ethylene-vinyl acetate copolymer powder (vinyl acetate content 20wt%), and continue mixing for 6 min, for a total mixing time of 10 min, to obtain the third mixture.
[0028] S5. Add the following additives to the third compound (based on 100 parts by weight of random copolymer polypropylene powder): 2400 ppm di(4-propoxybenzyl)sorbitol, 1000 ppm antioxidant 1010 (hindered phenol), 1000 ppm antioxidant 168 (phosphite), 600 ppm calcium stearate, and 400 ppm monoglyceride. Mix in a high-speed mixer at 900 r / min and 55°C for 12 min, then feed into a twin-screw extruder for melt extrusion granulation. The extruder temperatures (from feed section to die head) are controlled as follows: 170°C, 185°C, 185°C, 188°C, 188°C; screw speed: 230 r / min; vacuum level at the exhaust port: -0.08 MPa. The extruded melt was granulated underwater, cooled in a cooling water bath (water temperature 25℃), and air-dried at 45℃ for 12 minutes to obtain highly transparent random copolymer polypropylene granules.
[0029] Example 3 A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a Unipol gas-phase fluidized bed reactor, using a Ziegler-Natta catalyst (TiCl4 / MgCl2 supported catalyst) as the main catalyst, triethylaluminum as the co-catalyst (Al / Ti molar ratio = 60), and dicyclopentyldimethoxysilane as the external electron donor (Al / Si molar ratio = 8), polymer-grade propylene and polymer-grade ethylene are continuously fed into the reactor at a molar ratio of 40:1 for copolymerization. The reactor temperature is controlled at 62℃, the total reaction pressure at 3.3MPa, and the hydrogen and nitrogen atmospheres are controlled at 0.8% and 23.8% respectively. The polymerization time is 1.0 h. The polymer powder is discharged intermittently from the reactor to the product degassing chamber through a PDS discharge system. Nitrogen is injected to remove hydrocarbons, and high-temperature steam is injected to deactivate the catalyst, yielding random copolymer polypropylene powder.
[0030] S2. Based on 100 parts by mass of the above random copolymer polypropylene powder, add 4.5 parts by mass of hydrogenated C9 petroleum resin fine powder (softening point 110℃, number average molecular weight 1000, pre-ground to 150 mesh) to a high-speed mixer and mix for 15 minutes at a speed of 900 r / min and a temperature of 60℃. During the mixing process, turn on the cooling water jacket to control the temperature and obtain the first mixture.
[0031] S3. Take nano-calcium carbonate powder (particle size 60nm, specific surface area 20m²). 2 The nano-calcium carbonate (6g) was placed in a high-speed modifier and heated to 110°C. Stearic acid (1.2wt% of the nano-calcium carbonate mass) was pre-melted at 85°C and then uniformly sprayed into the modifier using an atomizing spray method. The mixture was mixed and modified for 25 minutes at a stirring speed of 1200 r / min. After cooling to room temperature, the mixture was mechanically pulverized and depolymerized to obtain active nano-calcium carbonate powder. 3.5 parts by mass of the above active nano-calcium carbonate were added to the first mixture and mixed for 10 minutes in a high-speed mixer at a speed of 700 r / min and a temperature of 55°C to obtain the second mixture.
[0032] S4. First, add 1.0 part by mass of ethylene-acrylic acid copolymer powder (acrylic acid content 8wt%) to the second mixture, and mix it in a high-speed mixer at a speed of 800 r / min and a temperature of 60℃ for 4 min to ensure that it is in full contact with the nano calcium carbonate powder; then add 2 parts by mass of ethylene-vinyl acetate copolymer powder (vinyl acetate content 20wt%), and continue mixing for 6 min, for a total mixing time of 10 min, to obtain the third mixture.
[0033] S5. Add the following additives to the third compound (based on 100 parts by weight of random copolymer polypropylene powder): 2600 ppm di(4-propoxybenzyl)sorbitol, 1000 ppm antioxidant 1010 (hindered phenol), 1000 ppm antioxidant 168 (phosphite), 600 ppm calcium stearate, and 400 ppm monoglyceride. Mix in a high-speed mixer at 900 r / min and 55°C for 12 min, then feed into a twin-screw extruder for melt extrusion granulation. The extruder temperatures (from feed section to die head) are controlled as follows: 170°C, 185°C, 185°C, 188°C, 188°C; screw speed: 230 r / min; vacuum level at the exhaust port: -0.08 MPa. The extruded melt was granulated underwater, cooled in a cooling water bath (water temperature 25℃), and air-dried at 45℃ for 12 minutes to obtain highly transparent random copolymer polypropylene granules.
[0034] Example 4 A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a Unipol gas-phase fluidized bed reactor, using a Ziegler-Natta catalyst (TiCl4 / MgCl2 supported catalyst) as the main catalyst, triethylaluminum as the co-catalyst (Al / Ti molar ratio = 60), and dicyclopentyldimethoxysilane as the external electron donor (Al / Si molar ratio = 8), polymer-grade propylene and polymer-grade ethylene are continuously fed into the reactor at a molar ratio of 45:1 for copolymerization. The reactor temperature is controlled at 63℃, the total reaction pressure at 3.45MPa, and the hydrogen and nitrogen atmospheres are controlled at 0.8% and 23.8% respectively. The polymerization time is 1.0 h. The polymer powder is discharged intermittently from the reactor to the product degassing chamber through a PDS discharge system. Nitrogen is injected to remove hydrocarbons, and high-temperature steam is injected to deactivate the catalyst, yielding random copolymer polypropylene powder.
[0035] S2. Based on 100 parts by mass of the above random copolymer polypropylene powder, add 6 parts by mass of hydrogenated C9 petroleum resin fine powder (softening point 110℃, number average molecular weight 1500, pre-ground to 150 mesh) to a high-speed mixer and mix for 15 minutes at a speed of 900 r / min and a temperature of 60℃. During the mixing process, turn on the cooling water jacket to control the temperature and obtain the first mixture.
[0036] S3. Take nano-calcium carbonate powder (particle size 80nm, specific surface area 20m²). 2The nano-calcium carbonate (6g) was placed in a high-speed modifier and heated to 110°C. Stearic acid (1.2wt% of the nano-calcium carbonate mass) was pre-melted at 85°C and then uniformly sprayed into the modifier using an atomizing spray method. The mixture was mixed and modified for 25 minutes at a stirring speed of 1200 r / min. After cooling to room temperature, the mixture was mechanically pulverized and depolymerized to obtain active nano-calcium carbonate powder. Five parts by mass of the above active nano-calcium carbonate were added to the first mixture and mixed for 10 minutes in a high-speed mixer at a speed of 700 r / min and a temperature of 55°C to obtain the second mixture.
[0037] S4. First, add 1.5 parts by mass of ethylene-acrylic acid copolymer powder (acrylic acid content 10wt%) to the second mixture, and mix it in a high-speed mixer at a speed of 800 r / min and a temperature of 60℃ for 4 min to ensure that it is in full contact with the nano calcium carbonate powder; then add 3 parts by mass of ethylene-vinyl acetate copolymer powder (vinyl acetate content 28wt%), and continue mixing for 6 min, for a total mixing time of 10 min, to obtain the third mixture.
[0038] S5. Add the following additives to the third mixture (based on 100 parts by weight of random copolymer polypropylene powder): 3000 ppm di(4-propoxybenzyl)sorbitol, 1000 ppm antioxidant 1010 (hindered phenol), 1000 ppm antioxidant 168 (phosphite), 600 ppm calcium stearate, and 400 ppm monoglyceride. Mix in a high-speed mixer at 900 r / min and 55°C for 12 min, then feed into a twin-screw extruder for melt extrusion granulation. The extruder temperatures (from feed section to die head) are controlled as follows: 170°C, 185°C, 185°C, 188°C, 188°C; screw speed: 230 r / min; vacuum level at the exhaust port: -0.08 MPa. The extruded melt was granulated underwater, cooled in a cooling water bath (water temperature 25℃), and air-dried at 45℃ for 12 minutes to obtain highly transparent random copolymer polypropylene granules.
[0039] Example 5 A method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process includes the following steps: S1. In a Unipol gas-phase fluidized bed reactor, using a Ziegler-Natta catalyst (TiCl4 / MgCl2 supported catalyst) as the main catalyst, triethylaluminum as the co-catalyst (Al / Ti molar ratio = 60), and dicyclopentyldimethoxysilane as the external electron donor (Al / Si molar ratio = 8), polymer-grade propylene and polymer-grade ethylene are continuously fed into the reactor at a molar ratio of 38:1 for copolymerization. The reactor temperature is controlled at 60℃, the total reaction pressure at 3.20 MPa, and the hydrogen and nitrogen atmospheres are controlled at 0.8% and 23.8% respectively. The polymerization time is 1.0 h. The polymer powder is discharged intermittently from the reactor to the product degassing chamber through a PDS discharge system. Nitrogen is injected to remove hydrocarbons, and high-temperature steam is injected to deactivate the catalyst, yielding random copolymer polypropylene powder.
[0040] S2. Based on 100 parts by mass of the above random copolymer polypropylene powder, add 3 parts by mass of hydrogenated C9 petroleum resin fine powder (softening point 110℃, number average molecular weight 800, pre-ground to 150 mesh) into a high-speed mixer and mix for 15 minutes at a speed of 900 r / min and a temperature of 60℃. During the mixing process, turn on the cooling water jacket to control the temperature and obtain the first mixture.
[0041] S3. Take nano-calcium carbonate powder (particle size 40nm, specific surface area 20m²). 2 The nano-calcium carbonate (6g) was placed in a high-speed modifier and heated to 110°C. Stearic acid (1.2wt% of the nano-calcium carbonate mass) was pre-melted at 85°C and then uniformly sprayed into the modifier using an atomizing spray method. The mixture was mixed and modified for 25 minutes at a stirring speed of 1200 r / min. After cooling to room temperature, the mixture was mechanically pulverized and depolymerized to obtain active nano-calcium carbonate powder. Two parts by mass of the above active nano-calcium carbonate were added to the first mixture and mixed for 10 minutes in a high-speed mixer at a speed of 700 r / min and a temperature of 55°C to obtain the second mixture.
[0042] S4. First, add 0.5 parts by mass of ethylene-acrylic acid copolymer powder (acrylic acid content 6wt%) to the second mixture, and mix it in a high-speed mixer at a speed of 800 r / min and a temperature of 60℃ for 4 min to ensure that it is in full contact with the nano calcium carbonate powder; then add 1 part by mass of ethylene-vinyl acetate copolymer powder (vinyl acetate content 18wt%), and continue mixing for 6 min, for a total mixing time of 10 min, to obtain the third mixture.
[0043] S5. Add the following additives to the third compound (based on 100 parts by weight of random copolymer polypropylene powder): 2200 ppm di(4-propoxybenzyl)sorbitol, 1000 ppm antioxidant 1010 (hindered phenol), 1000 ppm antioxidant 168 (phosphite), 600 ppm calcium stearate, and 400 ppm monoglyceride. Mix in a high-speed mixer at 900 r / min and 55°C for 12 min, then feed into a twin-screw extruder for melt extrusion granulation. The extruder temperatures (from feed section to die head) are controlled as follows: 170°C, 185°C, 185°C, 188°C, 188°C; screw speed: 230 r / min; vacuum level at the exhaust port: -0.08 MPa. The extruded melt was granulated underwater, cooled in a cooling water bath (water temperature 25℃), and air-dried at 45℃ for 12 minutes to obtain highly transparent random copolymer polypropylene granules.
[0044] Comparative Example 1 Comparative Example 1: Compared with Example 4, hydrogenated C9 petroleum resin was not added in step S2, while the remaining steps and dosages were completely identical.
[0045] Comparative Example 2: Compared with Example 4, no active nano-calcium carbonate was added in step S3, while the remaining steps and dosages were completely identical.
[0046] Comparative Example 3: Compared with Example 4, ethylene-acrylic acid copolymer and ethylene-vinyl acetate copolymer were not added in step S4, while the remaining steps and amounts were completely the same.
[0047] Comparative Example 4: Compared with Example 4, no ethylene-acrylic acid copolymer was added in step S4, while the remaining steps and amounts were completely identical.
[0048] Comparative Example 5: Compared with Example 4, no ethylene-vinyl acetate copolymer was added in step S4, while the remaining steps and amounts were completely identical.
[0049] Comparative Example 6: Compared with Example 4, the nucleating and clearing agent di(4-propoxybenzyl)sorbitol was not added in step S5, while the remaining steps and dosages were completely identical.
[0050] Comparative Example 7: Compared with Example 4, in step S3, the nano-calcium carbonate was not treated with stearic acid surface modification (untreated nano-calcium carbonate powder was used directly), and the remaining steps and amounts were completely the same.
[0051] Comparative Example 8: Compared with Example 4, the temperatures of each section of the extruder in step S5 for melt extrusion granulation were increased to 200°C, 215°C, 230°C, 230°C, and 220°C (i.e., conventional high-temperature processing was adopted), while the remaining steps and dosages were completely identical.
[0052] Comparative Example 9: Compared with Example 4, in step S4, the ethylene-acrylic acid copolymer and the ethylene-vinyl acetate copolymer were added simultaneously (instead of sequentially), and the remaining steps and amounts were completely identical.
[0053] Performance testing The polypropylene granules obtained in Examples 1-5 and Comparative Examples 1-9 were injection molded into standard test specimens in an injection molding machine at a processing temperature of 200°C (230°C for Comparative Example 8). The injection pressure was 90 MPa, the holding pressure was 55 MPa, the mold temperature was 25°C, and the cooling time was 25 s. The following performance tests were performed on the molded specimens: Haze Test: An integrating sphere haze meter was used to test the haze and transmittance of 1 mm thick injection-molded sheet samples according to the ASTM D1003 standard method. Before testing, the samples were conditioned in an environment of 23±2℃ and 50±5%RH for no less than 24 hours. Five samples were tested in each group, and the average value was taken. Haze is defined as the percentage of scattered light flux transmitted through the sample to the total transmitted light flux.
[0054] Melt Flow Rate (MFR) Test: The melt flow rate of polypropylene granules was determined using a melt flow rate meter at 230℃ and a load of 2.16kg, in accordance with GB / T 3682.1-2018 standard. Each sample was cut at least 5 times and the average value was taken. Before the test, the granules were dried in a vacuum oven at 80℃ for 2 hours to remove moisture.
[0055] Tensile strength test: The tensile properties of the 1A dumbbell-shaped standard specimens were tested using a universal testing machine in accordance with GB / T 1040.2-2022 standard. The tensile speed was 50 mm / min, the test temperature was 23±2℃, and at least 5 specimens were tested in each group. The average value was taken, and the tensile strength (maximum stress) and elongation at break were recorded.
[0056] Bending modulus test: According to GB / T 9341-2024 standard, a universal testing machine was used to perform a three-point bending test on a standard rectangular specimen of 80mm×10mm×4mm. The span was 64mm, the loading speed was 2mm / min, the test temperature was 23±2℃, and no less than 5 specimens were tested in each group. The average value was taken, and the bending modulus (the slope of the initial linear segment of the bending stress-strain curve) was recorded.
[0057] Cantilever beam notched impact strength test: In accordance with GB / T 1843-2024 standard, a cantilever beam impact testing machine was used to conduct notched impact tests on standard 80mm×10mm×4mm specimens. The notch type was Type A (notch radius 0.25mm, notch depth 2mm), the test temperature was 23±2℃, and at least 10 specimens were tested in each group. The average value was recorded, and the notched impact strength (energy absorbed per unit area at fracture) was recorded.
[0058] Heat distortion temperature test: In accordance with GB / T 1634.2-2019 standard, the heat distortion temperature of the standard specimens was tested using a heat distortion Vicat softening point tester. The applied stress was 0.45 MPa, the heating rate was 120℃ / h, and the temperature at which the specimen deformed by 0.25 mm under bending load was taken as the heat distortion temperature. The average value of no less than 3 specimens was taken for each test group.
[0059] Table 1: Compared to Example 4, Comparative Example 1 (without petroleum resin) showed a 1.7 percentage point increase in haze, indicating that hydrogenated C9 petroleum resin made a significant contribution to improving transparency, while the mechanical properties remained essentially unchanged, confirming that petroleum resin mainly plays a role in enhancing transparency rather than mechanical reinforcement.
[0060] Compared to Example 4, Comparative Example 2 (without nano-calcium carbonate) showed a 5.9 MPa decrease in tensile strength and a 455 MPa decrease in flexural modulus, indicating a significant degradation in mechanical properties. This fully demonstrates the irreplaceable role of nano-calcium carbonate in mechanical reinforcement. Furthermore, due to the absence of nano-calcium carbonate as a scattering source in the system, the haze was actually lower despite the addition of EVA / EAA, verifying that the introduction of CaCO3 was indeed the direct cause of the increased haze. The notched impact strength was 5.2 kJ / m. 2 Although it is higher than that of Comparative Example 3 without EVA / EAA protection, it is lower than that of Example 4, indicating that nano-calcium carbonate also makes a positive contribution to improving toughness under the optimized EVA / EAA interface conditions.
[0061] Compared to Example 4, Comparative Example 3 (without EVA and EAA) showed a sharp increase in haze to 9.3%, indicating severe agglomeration of nano-calcium carbonate in the absence of interfacial regulation, forming numerous light scattering centers. Simultaneously, the notched impact strength decreased to 4.9 kJ / m². 2 This demonstrates that the rubber elastic toughening contribution of EVA / EAA is also crucial for maintaining the material's toughness. Comparative Example 4 (without EAA) and Comparative Example 5 (without EVA), lacking only one interface-regulating component, showed haze increases to 7.1% and 6.4%, respectively, both significantly higher than Example 4 (3.9%), indicating that the synergistic effect of both EAA and EVA components is indispensable. The haze deterioration in Comparative Example 4 (without EAA) was more severe, confirming that the preferential adsorption of EAA carboxyl groups on the calcium carbonate surface is a key step in constructing an effective interface layer.
[0062] Compared to Example 4, Comparative Example 6 (without transparent agent) showed a significant increase in haze, but its mechanical properties remained essentially unchanged. This indicates that the nucleating transparent agent is one of the core components for achieving low haze, and its anti-reflection mechanism is independent of and synergistically complementary to that of petroleum resin.
[0063] Compared to Example 4, Comparative Example 7 (CaCO3 without surface treatment) showed an increase in haze to 8.2% and a decrease in notched impact strength to 5.0 kJ / m. 2 This indicates that the unmodified nano-calcium carbonate has poor interfacial compatibility with the polypropylene matrix, resulting in poor dispersion and severe agglomeration, which impairs both transparency and reduces toughness.
[0064] Compared to Example 4, Comparative Example 9 (with simultaneous addition of EVA and EAA) showed an increase in haze from 3.9% to 5.2%, indicating that when EAA was added simultaneously, it could not preferentially occupy the calcium carbonate surface to form a dense inner layer. This reduced the orderliness and density of the interface control layer, resulting in decreased dispersion and optical isolation effects. Although this difference was not as dramatic as in Comparative Example 3 (9.3%) without EVA / EAA, it was still observable, confirming the importance of the stepwise addition sequence of EAA followed by EVA for constructing an effective synergistic interface modification layer.
[0065] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing high-transparency random copolymer polypropylene by low-temperature processing based on Unipol process, characterized in that, Includes the following steps: S1. In a gas-phase fluidized bed reactor, propylene and ethylene monomers are copolymerized under the action of a catalyst to obtain random copolymer polypropylene powder. S2. Add hydrogenated petroleum resin to the random copolymer polypropylene powder and mix evenly to obtain the first mixture. S3. Add nano-calcium carbonate to the first mixture and mix evenly to obtain the second mixture; S4. Add ethylene-acrylic acid copolymer and ethylene-vinyl acetate copolymer to the second mixture in sequence, mix evenly, and obtain the third mixture. S5. Add nucleating and clarifying agents and processing aids to the third mixture, mix evenly, and then perform melt extrusion granulation. The maximum temperature of the extrusion granulation process shall not exceed 200°C to obtain highly transparent random copolymer polypropylene particles.
2. The method for preparing high-transparency random copolymer polypropylene based on the Unipol process at low temperature according to claim 1, wherein the molar ratio of propylene to ethylene in step S1 is (38-45):
1.
3. The method for preparing high-transparency random copolymer polypropylene by low-temperature processing based on Unipol process according to claim 2, wherein the catalyst in step S1 is a Ziegler-Natta catalyst; The copolymerization conditions are as follows: reactor temperature controlled at 60-63℃, and total reaction pressure at 3.20-3.45MPa.
4. The method for preparing high-transparency random copolymer polypropylene based on the Unipol process at low temperature according to claim 1, wherein the hydrogenated petroleum resin in step S2 is a hydrogenated C9 petroleum resin with a number average molecular weight of 800-1500.
5. The method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process according to claim 4, wherein the mass ratio of the random copolymer polypropylene powder to the hydrogenated petroleum resin is 100:(3-6).
6. The method for preparing low-temperature processed high-transparency random copolymer polypropylene based on Unipol process according to claim 1, wherein the mass ratio of the random copolymer polypropylene powder to nano-calcium carbonate in step S3 is 100:(2-5). Preferably, the nano-calcium carbonate is surface-treated activated nano-calcium carbonate with a particle size of 40–80 nm and a specific surface area ≥20 m². 2 / g; The active nano-calcium carbonate is stearic acid-modified nano-calcium carbonate.
7. The method for preparing high-transparency random copolymer polypropylene based on the Unipol process at low temperature according to claim 1, wherein the amount of ethylene-acrylic acid copolymer added in step S4 is 0.5-1.5 wt% of the random copolymer polypropylene powder, and the amount of ethylene-vinyl acetate copolymer added is 1-3 wt% of the random copolymer polypropylene powder; The ethylene-acrylic acid copolymer contains 6-10 wt% acrylic acid; the ethylene-vinyl acetate copolymer contains 18-28 wt% vinyl acetate.
8. The method for preparing high-transparency random copolymer polypropylene based on the Unipol process at low temperature according to claim 1, wherein the nucleating transparent agent in step S5 is a sorbitol disubstituted derivative; and the amount of nucleating transparent agent added is 2200-3000 ppm based on 100 parts by mass of the random copolymer polypropylene powder.
9. The method for preparing high-transparency random copolymer polypropylene based on the Unipol process at low temperature according to claim 8, wherein the nucleating and transparentizing agent is di(4-propoxybenzyl)sorbitol; The processing aids include primary antioxidants, secondary antioxidants, acid removers, and release agents; The primary antioxidant is a hindered phenolic antioxidant, the secondary antioxidant is a phosphite antioxidant, the acid remover is calcium stearate, and the release agent is monoglyceride.
10. A low-temperature processed, highly transparent random copolymer polypropylene based on the Unipol process, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.